Agile-Scrum Methodology for Hospital Information System Development - Zulkifli, Zulkifli; Ratnasari, Ratnasari; Arifin, Yulyani; Habib, Cahya (Universitas Bina Darma, 2025)
Hospitals face significant challenges in managing large and complex data, and Hospital Information Systems (SIRS) are essential for supporting hospital operations. However, many SIRS projects experience delays and failures due to rigid development approaches. Agile-Scrum is proposed as a more flexible and adaptive solution, emphasizing collaboration and iterative processes to enhance the quality of healthcare services. This qualitative case study, conducted in a hospital with an internal development team, used observations, document analysis, and semi-structured interviews with 10 participants, including developers, a Scrum Master, and key hospital stakeholders. The findings indicate that implementing Agile-Scrum led to a 35% increase in team collaboration, a 40% improvement in responsiveness to changing requirements, and a 30% boost in overall project efficiency. The study highlights the effectiveness of Agile-Scrum in managing the complexities of SIRS development, especially through backlog organization, sprint planning, and stakeholder feedback. The study suggests further research to assess the long-term impact of Agile-Scrum in other information system development contexts.